PERAN SUAMI MENURUNKAN KECEMASAN SAAT PROSES PERSALINAN - Ari Shanti, Elvika Fit (MEDIA ILMU KESEHATAN, 2012)
Background: Labor or childbirth is a very tough fight for a mother; the mother in this process does not escape from fear. Fear is usually caused by the lack of emotional support, especially from the husband. Most mothers who deliver babies rarely accompanied by their husband are more depressed after childbirth. Husband's presence during childbirth makes a shorter delivery time, so the pain is also reduced, and the birth canal laceration is also rarer because the birth canal is more elastic. However, until present, husbands have not been able to show their full support for deliveries where 68% of births are not accompanied by husbands. Suami SIAGA (ALERT Husband) program implementation has not been carried out and has not become routine antenatal care program. This can affect the psychology of the mother. Objective: To determine the effect of husband support quality on the anxiety experienced by mothers in labor at BPS (privately practicing midwife) Endang Purwaningsih of Bantul in Yogyakarta. Methods: This was a quasi experimental study with one group pretest-posttest design without control. The sample size was 30 that had been adapted to the criteria, ie labor accompanied by the husband, the active phase of the first stage of labor, singleton pregnancy, and parity 1-3. Sampling technique used Accidential Sampling. Data were collected by using observation sheets and check lists. Analysis of the data used parametric technique ie normality test using Kolmogorov Smirnov and inferential analysis with paired t-test. Results: The results of the husband support quality assessment showed that the average of husband support was good. The measurement result of maternal anxiety levels was known that pretest and posttest values showed the same condition that most of the mothers in labor had severe levels of anxiety (pretest by 60% and posttest by 53.3%). However, the percentage in the level of anxiety ie panic declined, from 6.6% to 3.3%. The data were normally distributed and paired t-test analysis obtained p value = 0.04 (p <0.05). Conclusion: The higher level of husband support quality led to the lower level of anxiety experienced by mothers in childbirth. Husband is expected to provide emotional support and pay attention to the wife during labor. Keywords: Support quality, anxiety, childbirth